2019
DOI: 10.1016/j.jfineco.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off theory of ownership and capital structure

Abstract: This paper determines the optimal ownership share held by a unit into a second unit, when both face a tax-bankruptcy trade-off. Full ownership is optimal when the first unit has positive debt, because dividends help avoid its default. Positive debt is, in turn, optimal when its corporate tax rate exceeds a threshold; and/or Thin Capitalization Rules place an upper limit on the debt level in the second unit, and/or the Volcker Rule bans bailout transfers to the second unit. Full ownership is no longer optimal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 56 publications
1
22
0
1
Order By: Relevance
“…The departure is critical as the authors discover that, by enabling both coin-surance and deflection of contagion risk, conditional guarantees allow for an asymmetric shift of the leverage profile across BG's affiliates jointly with an overall expanded debt capacity. Close to the network formation spirit of my paper, Nicodano and Regis (2019) expands Luciano and Nicodano (2014) by proposing a general trade-off model in which a controlling entity optimally decides the ownership share of two subsidiaries, thus allowing for truly complex structures. Depending on the tax saving -contagion trade-off, these range from hierarchical (with full or partial subsidiary ownership by parent) to horizontal.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The departure is critical as the authors discover that, by enabling both coin-surance and deflection of contagion risk, conditional guarantees allow for an asymmetric shift of the leverage profile across BG's affiliates jointly with an overall expanded debt capacity. Close to the network formation spirit of my paper, Nicodano and Regis (2019) expands Luciano and Nicodano (2014) by proposing a general trade-off model in which a controlling entity optimally decides the ownership share of two subsidiaries, thus allowing for truly complex structures. Depending on the tax saving -contagion trade-off, these range from hierarchical (with full or partial subsidiary ownership by parent) to horizontal.…”
Section: Related Literaturementioning
confidence: 99%
“…In terms of the financing advantage, Almeida et al (2011) show that groups use internal revenues to set up or acquire capital-intensive firms, which are more likely to be constrained in financial markets. Parallel to (or on top of) this channel, tax-saving and financial resilience may shape the architecture and the direction of inter-firm capital allocations (see, in particular, Regis, 2019 andLuciano andNicodano, 2014). I postpone the discussion on this literature to Section 1.1.…”
Section: Introductionmentioning
confidence: 99%
“…This was controlled because previous studies have found firm size to be positively related to leverage (Friend and Lang, 1988;, whereas others have found it to be negatively related . Large firms may use more leverage in their capital structure because of the availability of tangible assets to secure debts (Nicodano & Regis, 2019) The study also controlled for firm performance, because of strong indications of its effect on capital structure (Le and Phan, 2017). For example, pecking order theory postulates that firms generating profits finance their assets from retained profits first before resorting to debts.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Recent scholars explore capital structure and monetary policy (Grosse-Rueschkamp et al, 2019), asymmetric information, debt capital, (Lemmon and Jaime, 2019), optimal leverage, profitability (Chen et al, 2019), trade-off theory of ownership (Nicodano and Regis, 2019) and bankruptcy choice (Antill and Grenadier, 2019). Largely, literature seems to converge on the notion that an optimal capital structure is required to minimise cost of capital, thereby maximising shareholder's value.…”
Section: Introductionmentioning
confidence: 99%